Keratinolytic fungi in illegal feather dump sites of condoray – Ayacucho: Isolation, characterization, and degradative potential - Chuchón-Martínez, Saúl Alonso; Delgadillo-Coronado, Pedro Mauricio; Gastelu-Quispe, Rilder Nemesio; Cruz, Ruth Elsa Huaman-De La; Rivera-Villar, Jime Jack; Marín-Sánchez, Obert (Edelweiss Applied Science and Technology, 2025)
This study explores the potential of keratinolytic fungi for feather waste degradation. Soil and feather samples were collected from the clandestine feather dump in Condoray-Ayacucho and processed at the UNSCH Environmental Microbiology Laboratory. Fungi were isolated using Bushnell Haas (B-H) medium supplemented with sterilized chicken feathers, and proteolytic strains were selected using milk agar (LA). Of the 18 strains isolated, three (C.S.4, C.S.7, and C.P.2.1) exhibited significant protease activity, forming halos of 12–17 mm. Their feather-degrading capacity was assessed in B-H medium with 1% feathers, inoculated with 250 µl of spore solution (10⁶ spores/100 µl), and incubated at 25°C for 8 days with manual agitation. Strain C.P.2.1 showed the highest degradation, reducing feather weight by 12%, followed by C.S.7 (10%) and C.S.4 (8%). A gradual increase in pH and protein release was observed, reaching 0.40 mg/ml for C.P.2.1, 0.32 mg/ml for C.S.7, and 0.15 mg/ml for C.S.4. These findings highlight the potential of keratinophilic fungi for enzymatic degradation of keratin. Statistical analysis revealed no significant differences among strains, but a significant difference compared to the control (p<0.05, Tukey test).